Compact dual-frequency PIFA designs using LC resonators. - Lui, G.K.H (IEEE Transactions on antennas and propagation)
We report our investigation into single-feed dual-frequency planar inverted F antenna (PIFA) designs which make use of LC resonators (or ?RF traps?). We introduce three basic methods for incorporating the LC resonator into the PIFA, including a variant of the meandering PIFA. Experimental results are provided and these show that dual-frequency operation at 900 (cellular systems) and 1800 MHz (personal communication systems) can be achieved for all three designs